Student Digital Literacy in the Age of Technology: A PRISMA-Based Systematic Review - Nur Azizah Putri Hasibuan; Gita Wulandari (Universitas Sebelas Maret, 2026)
Digital literacy is an essential competency that students must possess in an era of rapidly advancing information technology. Digital literacy is not only related to the ability to use devices but also encompasses the skills to access, understand, evaluate, and utilize digital information in a critical, ethical, and responsible manner. This study aims to examine students’ digital literacy levels, the factors influencing them, the use of digital media in learning, the challenges in its development, and the urgency of digital literacy for students based on previous research findings. This study employed the Systematic Literature Review (SLR) method using the PRISMA approach. The research process was conducted on 104 articles from various national and international journal databases from 2020 to 2025. After undergoing title and abstract screening, full-text eligibility checks, and the application of inclusion and exclusion criteria, 18 articles were selected for thematic analysis. The results of the study indicate that students’ digital literacy levels generally fall into the low to moderate categories. Factors influencing students’ digital literacy include the availability of technological resources, teacher competence, parental support, the school environment, and curriculum policies. The use of digital media in learning has been shown to improve students’ digital literacy when accompanied by appropriate guidance. However, various challenges remain, such as limited access to technology, low understanding of digital ethics, and digital divides between regions. Therefore, digital literacy needs to be developed systematically and sustainably within the education sector.